Sensor óptico de frentes de onda com quadricélula de dupla eficiência quântica em tecnologia CMOS padrão - Luciana Pedrosa Salles (2010)
This work presents an alternative layout for optical HartmannShack WaveFront Sensor (WFS), which is composed of Position-Sensitive Detectors (PSDs) of the Quad-Cell (QC) type, with two different sensitivity regions (i.e. two different quantum efficiencies - QCdouble). The proposed layout is compatible with the standard Complementary MetalOxide-Semiconductor (CMOS) technology. Mathematical models are proposed, described and used to characterize the WFS and QC parameters for ophthalmologic applications. The simulation results using QCdouble or convectional QC in WFS show wavefront reconstruction error with QCdouble smaller than that with the conventional one, when using linear approximation of the QC response. Smaller measurement errors are obtained when compared to conventional wavefront sensors, since the quad-cell response can be better approximated to a linear response due to the quad-cell architecture which compensates the usually non-linear response of conventional QC for radially symmetric light spots. In addition, some project parameters are discussed based on numerical simulations and experimental results, in order to make the sensor suitable for high-order ocular aberration (optical distortion) measurements and lens characterization.